KAJIAN KARAKTER FISIOLOGIS VARIETAS PADI SAWAH PADA BUDIDAYA SECARA ORGAN - ACHMAD FATCHUL AZIEZ; Agus Budiyono; Daryanti; Wiyono; Setie Harieni; Dwi Susilo Utami (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
The reality in the field shows that not all lowland rice varieties which include local varieties, old superior varieties, new superior varieties and new types of varieties are suitable for organic cultivation because each group of varieties has different physiological characters. This research was carried out with the aim of determining the suitable lowland rice varieties for organic cultivation based on physiological characters. The research was carried out through pot experiments to determine the suitability of lowland rice varieties including local varieties, old varieties, new varieties, and new types of superior varieties in organic cultivation based on their physiological characteristics. with an altitude of 113 m above sea level with inceptisol soil types and tropical climate. The results showed that organic cultivation did not reduce root permeability to N uptake except for Cisedane variety. Organic cultivation lowered the KPK for the roots of the IR64, Cianjur and Mentikwangi varieties, but increased the KPK for the roots of the Pandanwangi and Cisedane varieties. The uptake rate of N, P, and K roots in organic cultivation was not different from conventional cultivation. The uptake of N roots in organic cultivation was lower than conventional cultivation. The uptake of N, P, and K by roots between varieties was not different. Organic cultivation reduced the uptake of N stems of varieties IR64, Mentikwangi and Cisedane. Among the varieties tested, there was no difference in N uptake in conventional or organic cultivation. Organic cultivation reduced the P uptake of stems of IR64 and Mentikwangi varieties, Organic cultivation decreased total N uptake of Mentikwangi varieties. In conventional and organic cultivation, the plant N uptake of all tested rice varieties was no different.